Determination of L-Argininamide Based on Water-Soluble Fluorescent Conjugated Polymer-Aptamer - Hongliang Guan; Zhike He (Journal of Analytical Methods in Chemistry)
Water-soluble fluorescent conjugated polymer is a promising material which could be used as an optical platform in highly sensitive molecular sensors. In this paper, a simple label-free DNA sensor, which consisted of a poly(3-alkoxy-4-methylthiophene) and an aptamer, was used to detect L-argininamide (L-Arm). Due to the specific binding reaction between L-Arm and its aptamer, the proposed method can easily determinate the L-Arm through the recovery of fluorescence without any modification. Other ions or similar molecules had little effect on the detection. Moreover, there was a linear relationship between fluorescence intensity and the concentration of L-Arm. The detection limit of L-Arm was as low as 4.7 nM.